DUAL MODE IN-SERVICE TRAINING AS AN ALTERNATIVE MODEL FOR TEACHERS PROFESSIONAL (PD) IN INDONESIA - Widodo, Ari (International Journal of Education, 2011)
To improve the quality of education, the Indonesian government has been launching anumber of teachers’ professional development (PD) programs. These, however, broughtlittle impact on the improvement of teaching practice and students’ achievement. Thispaper reports a two-year research project on a dual mode in-service training program thatcombines a classical in-service training and training via internet. The first year focused onidentifying teachers’ professional needs while the second year focused on the developmentof training packages and tried out the training model. The study reveals that scienceteachers need training both on subject matter and pedagogy. In addition to the traditionalface to face workshop, they also expect online training via internet since it allows them tohave flexibility in accessing the materials as well as consultation with experts. This studysuggests that participation in dual mode teachers PD improve teachers’ understanding ofsubject matter and pedagogy.Key words: dual mode; in-service training; professional development; science teacher